The removal of cephalexin antibiotic in aqueous solutions by ultrasonic waves/hydrogen peroxide/nickel oxide nanoparticles (US/H2O2/NiO) hybrid process - Seid-Mohammadi, Abdolmotaleb; Asgarai, Ghorban; Ghorbanian, Zeinab; Dargahi, Abdollah (Separation science and technology, 2020)
Antibiotics are non-biodegradable and can remain for a long time at aquatic environments and they have a big potential bio-accumulation in the environment. The antibiotics are broadly metabolized by humans, animals and plants and they or their metabolites, after metabolization, are entered into the aquatic environment. This study aimed to optimize the operational parameters by Taguchi design and to carry out the kinetic studies for removal of cephalexin antibiotic from aqueous solutions by US/H 2 O 2 /NiO hybrid process. This experimental study was performed on a laboratory scale in a 500 mL pyrex-made reactor. The main operational parameters to influence the US/H 2 O 2 /NiO process were identified as the initial concentration of CEX (20-80 mg/L), hydrogen peroxide (H 2 O 2 ) (10-40 mL/L), NiO nanoparticle (2.5-10 mg/L) and reaction time (15-90 min) and therefore, the influence of these factors were studied. Under optimum conditions (pH = 3, reaction time = 90 min, CEX = 40 mg/L, NiO = 7.5 mg/L and H 2 O 2 = 30 mL/L) and using the US/H 2 O 2 /NiO process, the removal efficiencies of CEX, COD and TOC were 93.86%, 72.46% and 54.55%, respectively. The percentage contribution of each factor was also determined. Results introduced the solution pH as the most powerful factor, and its percentage contribution value was up to 94% in the studied process. It was also identified that the removal of CEX antibiotic using the hybrid process obeys the pseudo-first-order kinetics.